The quest for immunotherapy in atherosclerosis: CANTOS study, interleukin-1β and vascular inflammation - Bermúdez, Valmore; Rojas-Quintero, Joselyn; Velasco, Manuel (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Despite the monumental efforts directed into studying and describing the pathways, factors, genetic predisposition, and target-specific pharmacotherapy to atherosclerosis, ischemic heart disease, thrombotic cerebrovascular disease and peripheral artery disease are still responsible for 50% of all the deaths occurring in the developed world. The quest for a clear pathophysiology into atherosclerosis began with von Rokitansky’s incrustation theory, which evolved into the crucial role of platelets and thrombogenesis during acute coronary syndromes (1). Next, came the irritation theory postulated by Virchow, which detailed the presence of leukocytes in atherosclerotic plaques, suggesting the presence of chronic inflammation and progressive vessel deformation (1). By 1904, the term atherosclerosis was coined by Felix Jacob Marchand and 9 years later Nikolai Anichkov published that cholesterol alone can induce the vascular changes associated with atherosclerosis (1).